Інноваційна технологія вилучення та концентрування органічних домішок спирту в режимі керованої ректифікації - Булій, Юрій Володимирович; Шиян, Петро Леонідович; Дмитрук, Аркадій Павлович; Малигін, А. І. (My University, 2013)
Експериментально обґрунтовано доцільність впровадження у виробництво технології ректифікації в режимі керованих циклів затримки та переливу рідини; досліджено ступінь вилучення і кратність концентрування ключових органічних домішок спирту в умовах помірної та глибокої гідроселекції; доведено, що використання технології керованої ректифікації дозволяє понизити витрати гріючої пари на 40 %. Experimentally grounded expedience of applying in industry of technology of rectification in the mode of the guided delay and flowing of liquid loops; investigational degree of exception and multipleness of concentration of key organic admixtures of alcohol in the conditions of moderate and deep of selection by water. It is well-proven that at moderate of selection by water in a less measure retire etilbutirat, etilacetat, alcohols of fusel oil and izopropanol.The leadthrough of deep of selection by water allows to reduce in a deep blue liquid the concentration of aldehydes on 62,2 %, esteras on 26,1 %, higher alcohols of fusel oil on 82,2 %, izopropanol on 71,0 %, in a complete measure to withdraw etilbutirat, izobutilacetat, izoamilacetat, ethyl-acetate, to increase multipleness of concentration of aldehydes on 43,0 %, esteras on 46,7 %, alcohols of fusel oil on 54,0 %. Thus the charges of warming pair on the process of extract rectification diminish on 40 % and make 11-13 kg/dal that enters column.
Keywords: ректифікація; фазова рівновага; керовані цикли; масообмін; гідроселекція; переливні пристрої; rectification; phase equilibrium; guided cycles; mass-transfer; selection by water; flowing devices; кафедра біотехнології продуктів бродіння і виноробства